A flexibly controllable high-flux solar simulator for concentrated solar energy research from extreme magnitudes to uniform distributions. (April 2022) - Li, Jieyang; Hu, Jinpeng; Lin, Meng
Abstract: High-flux solar simulator (HFSS) is a useful lab-scale equipment for material, device, and prototype characterizations and testing via creating stable and controllable irradiation environments close to real solar concentrators. This study presents the design, building, and characterization of a flexibly controllable 40 kWe HFSS consisted of 4 × 10 kWe radiation modules at SUSTech enabling applications from photothermal to photoelectrochemical devices. A cylindrical reflector was designed at the focal plane as the optical homogenizer for generating uniform flux profiles for concentrated photovoltaic and photoelectrochemical applications. Both indirect and direct calibration methods were performed, compared, and correlated. The measured results are shown a record high peak flux of 41.43 MW m −2, summing over all four lamps without the homogenizer, which is 91% higher than the highest value reported in the literature. The average flux and total power in a circular target with a radius of 50 mm are 2.25 MW m −2 and 17.57 kW, respectively, showing a high electricity-to-radiation efficiency of 43.93%. When adding the homogenizer, the total uniformity of the system was tripled. Highly uniform region with non-uniformity of only 1.76% can be identified meeting the ASTM class A standard in terms of spatial non-uniformity. In addition to solar thermal/thermochemical applications, this newly built HFSS enables applications in concentrated solar photovoltaics and photoelectrochemical devices and beyond. Graphical abstract: Image 1 Highlights: Design and characterization of a 40 kWe HFSS with a peak-flux of 41.43 MW m −2 . Consistent characterization results use both indirect and direct methods. The optimized homogenizer enables application beyond solar thermal. Highly uniform region with spatial non-uniformity of only 1.76% can be identified.